UJI EFEK ANTIINFLAMASI EKSTRAK ETANOL DAN EKSTRAK n- HEKSAN BIJI JINTAN HITAM (Nigella sativa L.) TERHADAP MENCIT (Mus musculus). - Mukhriani Mukhriani; Faridha Yenny Nonci; Fathiyah Nuhrang (Jurnal Farmasi UIN Alauddin Makassar, 2020)
Studies have been conducted testing anti-inflammatory effects of black cuminseed extract to mice with induced by subplantar albumin, wich to determine the effect and the concentration of the seed extract jintan hitam as an anti-inflammatory. This study was done by giving albumin as mediators of inflamatinon in the feet of mice, after which the black cumin seed n-Heksan extract to mice given orally with a dose of 1,2 g/kg BB, 2,4 g/kg BB, and 4,8 g/kg BB and carried out observations began after inducing albumin, up to 120 minutes. Na.diclofenac is used as a comparison at dose of 0,2 mg. Obtained inflammation percentage of black cumin seed n-Heksan extract with dose 1,2 g/kg BB is 17,5%, dose 2,4 g/kg BB is 18,06% and for dose 4,8 g/kg BB is 23,33%. For black cumin seed etanol extract given orally with a same dose of 1,2 g/kg BB, 2,4 g/kg BB, and 4,8 g/kg BB orally and carried out observations began after inducing albumin, up to 120 minutes. Na.diclofenac is used as a comparison at dose of 0,2 mg. Obtained inflammation percentage of black cumin seed etanol extract with dose 1,2 g/kg BB is 20,83%, dose 2,4 g/kg BB is 22,22% and for dose 4,8 g/kg BB is 24,72%.Doses of n-Heksan extract of seed black cumin and etanol extract of seed black cumin given to mice has antiinflammatory effects. This shows that n-Heksan extract of the seed black cumin and etanol extract of seed black cumin capable of inhibiting inflammation to mice induced by albumin. From the three doses, the best doses who give inhibiting inflammation is 4,8 g/kg BB for n-Heksan extract of seed black cumin and etanol extract of seed black cumin.